The Influence of Content Marketing and Influencers on Consumer Buying Interest Mediated by Brand Trust - Saputra, Arrijal Shonny; Padmantyo, Sri (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the influence of content marketing and social media influencers on consumer purchase intention, with brand trust examined as a mediating variable. Employing a quantitative causal design, data were collected via an online questionnaire targeting social media users in Surakarta who are at least 18 years old and have been active in the past six months. A purposive sampling technique was applied to recruit 100–200 respondents. While this approach enabled focused data collection, it may have introduced sampling bias and limited demographic diversity, thereby restricting the generalizability of the findings beyond the Surakarta area. The study employed a 5-point Likert scale and analyzed the data using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS 3 software. Results indicate that both content marketing and social media influencers positively and significantly influence brand trust. Engaging and informative content enhances brand credibility, while credible influencers foster emotional attachment to the brand. Furthermore, brand trust significantly drives purchase intention, highlighting its importance in consumer behavior. Both content marketing and influencers also directly affect purchase intention. However, brand trust does not mediate the relationship between content marketing and purchase intention, nor between influencers and purchase intention, suggesting the presence of other moderating variables such as price sensitivity or perceived product quality. These insights offer valuable implications for businesses seeking to build consumer trust and enhance digital marketing effectiveness, while also acknowledging the limitations in scope and sample representativeness.